Erythritol Availability in Bovine, Murine and Human Models Highlights a Potential Role for the Host Aldose Reductase during Brucella Infection - Barbier, Thibault; Machelart, Arnaud; Zúñiga-Ripa, Amaia; Plovier, Hubert; Hougardy, Charlotte; Lobet, Elodie; Willemart, Kevin; Muraille, Eric; De Bolle, Xavier; Van Schaftingen, Emile; Moriyón, Ignacio; Letesson, Jean-Jacques (Frontiers in Microbiology, 2017)
Erythritol is the preferential carbon source for most brucellae, a group of facultative intracellular bacteria that cause a worldwide zoonosis. Since this polyol is abundant in genital organs of ruminants and swine, it is widely accepted that erythritol accounts at least in part for the characteristic genital tropism of brucellae. Nevertheless, proof of erythritol availability and essentiality during Brucella intracellular multiplication has remained elusive. To investigate this relationship, we compared ∆eryH (erythritol-sensitive and thus predicted to be attenuated if erythritol is present), ∆eryA (erythritol-tolerant but shows reduced growth if erythritol is a crucial nutrient) and wild type B. abortus in various infection models. This reporting system indicated that erythritol was available but not required for B. abortus multiplication in bovine trophoblasts. However, mice and humans have been considered to lack erythritol, and we found that it was available but not required for B. abortus multiplication in human and murine trophoblastic and macrophage-like cells, and in mouse spleen and conceptus (fetus, placenta and envelopes). Using this animal model, we found that B. abortus infected cells and tissues contained aldose reductase, an enzyme that can account for the production of erythritol from pentose cycle precursors.